Infiltrative hepatocellular carcinoma with multiple lung metastasis completely cured using nivolumab: a case report - Ji Eun Han; Hyo Jung Cho; Soon Sun Kim; Jae Youn Cheong (Korean Liver Cancer Association, 2021)
The current Food and Drug Administration-approved systemic treatments for advanced hepatocellular carcinoma (HCC) include multikinase inhibitors (tyrosine kinase inhibitor [TKI]) and immune checkpoint inhibitors (ICIs). Among ICIs, nivolumab is used as second-line therapy for advanced HCC after sorafenib failure or patient intolerance. In this case, a patient with infiltrative HCC and portal vein tumor thrombosis was treated with hepatic arterial infusion chemotherapy (HAIC) and radiation therapy. New lung metastasis developed after HAICs; thus, lenvatinib treatment was initiated. However, the disease progressed. Thereafter, sorafenib treatment was initiated but he developed intolerance, with grade 3 sorafenib-related diarrhea. Subsequently, nivolumab was administered as rescue therapy. He demonstrated a partial response to nivolumab after the third treatment and viable HCCs in the lungs and liver completely disappeared after the 24th treatment. These findings suggest that nivolumab could be used as an effective rescue therapy for advanced HCC progression after TKI treatment.